Leg power and physical performance measures of top national track athletes - Amusa, L. O.; Toriola, A. L. (Journal of Exercise Science & Fitness, 2003)
In this study, we evaluated the mechanical-muscular factors of performance in track athletics by using tests of leg power and physical performance measures. The purposes of these tests were to help select the most likely prospects for each event as quickly as possible, and also allow the coach to locate talent in unsuspected areas. A total of 13 athletes with a mean age of [mean(SD)] 24.3(2.8) years were tested. They were all sprint (100m, 200m, and 400m) athletes. The Wingate Anaerobic Test (Wan T) was adopted for determining leg power output of peak power, minimum power, average power and power drop (fatigue index) using the Monark E-180 bicycle ergometer. Tests of physical performance included strength (arm and hand grips, leg lift and back lift), explosive power (vertical jump) and flexibility (sit and reach, shoulder lift and trunk extension). Data were analyzed descriptively. The sprinters` leg power output results were 651.75(60.7) W, 313.68(28.88) W, 486.84(37.63) W and -1.96(0.64) W.s-1 for peak power, minimum power, average power and power drop (fatigue index), respectively. These results indicate that although the subjects were all sprint athletes they were indeed heterogeneous. Mean explosive power was 51.84 kgm.sec-1; mean flexibility values were 34.05(1.56) cm, 30.53 (1.93) cm, 31.45 (1.89) cm for sit and reach, shoulder lift and trunk extension, respectively. The leg power outputs and explosive values were considered too low for sprint events. Similarly, the low values in the physical performance variables deserve the coaches` intervention to ensure the athletes` success in their events.